2019
DOI: 10.2134/cftm2018.12.0103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Methods of Pasture Rejuvenation for Improved Forage Production

Abstract: Methods to improving depleted forage stand by seeding, weed control, fertilizer application, and aeration were investigated. A combination of vegetation control + direct seeding improved forage yield, crude protein, and total digestible nutrients. A 2‐year combined forage yield for four methods increased profit from forage production. A 3‐year on‐farm study was conducted in northwestern Alberta to determine the effects of several pasture rejuvenation methods such as breaking and reseeding, spraying to control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…These results are similar to Omokanye et al (2018) who determined that spring sod-seeding a blend of smooth bromegrass, alfalfa, and cicer milkvetch species as a rejuvenation strategy was not economically feasible, with net losses per hectare, depending on site location with losses predicted at -$166 ha -1 and -$103 ha -1 over 3 yr. However, economic results are variable as a separate study by Omokanye et al (2019) reported net profit of $380 ha -1 over 2 yr, when sod-seeding a meadow bromegrass, orchardgrass, timothy and alfalfa blend, whereby seed cost was $131 ha -1 , and total rejuvenation cost was $236 ha -1 , which is $100 ha -1 lower than the current study total sod-seeding cost.…”
Section: Economic Analysiscontrasting
confidence: 66%
See 2 more Smart Citations
“…These results are similar to Omokanye et al (2018) who determined that spring sod-seeding a blend of smooth bromegrass, alfalfa, and cicer milkvetch species as a rejuvenation strategy was not economically feasible, with net losses per hectare, depending on site location with losses predicted at -$166 ha -1 and -$103 ha -1 over 3 yr. However, economic results are variable as a separate study by Omokanye et al (2019) reported net profit of $380 ha -1 over 2 yr, when sod-seeding a meadow bromegrass, orchardgrass, timothy and alfalfa blend, whereby seed cost was $131 ha -1 , and total rejuvenation cost was $236 ha -1 , which is $100 ha -1 lower than the current study total sod-seeding cost.…”
Section: Economic Analysiscontrasting
confidence: 66%
“…Although available forage at both sites was lower than levels measured in sainfoin/alfalfa pastures at Lethbridge by Sottie et al (2014), yields at Lanigan were similar to mixed grass pastures measured at Lanigan by Anez (2015). It is possible that the mechanical aeration and soil disturbance caused by seeding could contribute to some increase in yield (Davies 1989); however, other studies have reported no increase in forage yield from mechanical aeration (Omokanye et al 2019;Lardner 2000, Malhi et al 2000 Environment can cause significant year-to-year and seasonal variation in forage quality, due to alterations in aspects such as leaf/stem ratios, morphology, and chemical composition of the plant (Buxton and Fales 1994;Buxton 1996). Year to year variation may have been evident in the current study since start of trial forage quality was different between treatments and dependent on year.…”
Section: Botanical Composition Forage Yield Forage Quality and Soil N...mentioning
confidence: 62%
See 1 more Smart Citation
“…The importance of forage production lies in solving the problem of rational use of natural resources in agriculture, ensuring the balance of agricultural landscapes, the structure of sown areas, crop rotations, optimization of crop production, agriculture and animal husbandry. Increasing the productivity of fodder land is one of the most critical tasks of agricultural production, dictated by the need to maximize the productivity of the animals, in part through increasing the cost recovery for each fodder unit (1)(2)(3)(4)(5)(6)(7)(8). It should also be noted that over 2/3 of haylands and pasture fields of the Central Non-Black Earth Zone in the Russian Federation are degrading, which is due to the deterioration of the flora, the prevalence of low-value plant species, the formation of a long-term sod layer that is resistant to mechanical stresses and the disruption of the air and water regime of the surface soil (1).…”
Section: Introductionmentioning
confidence: 99%